Interdental Cleaning Is Associated with Decreased Oral Disease Prevalence. (July 2018) - Marchesan, J.T.; Morelli, T.; Moss, K.; Preisser, J.S.; Zandona, A.F.; Offenbacher, S.; Beck, J.
The purpose of this study was to evaluate the associations between interdental cleaning behavior and the prevalence of caries and periodontal disease and numbers of missing teeth, with data from the National Health and Nutrition Examination Survey (2011 to 2012 and 2013 to 2014). Analysis included the following parameters: interproximal clinical attachment level (iCAL) ≥3 mm, interproximal probing depth (iPD) ≥4 mm, number of coronal and interproximal caries, number of missing teeth, ≥1 surfaces with coronal caries, and periodontal profile classes (PPCs). Chi-square was used for bivariate associations. Associations of interdental cleaning with outcomes were assessed with multiple linear regression and generalized logit regression, adjusting for age, race, sex, diabetes, smoking, education, dental visits, and sugar consumption. Nonusers had a significantly higher percentage of sites with iCAL ≥3 mm and iPD ≥4 mm as compared with individuals who used interdental cleaning devices ( P < 0.0001). Individuals with a higher frequency of cleaning (4 to 7×/wk) had a significantly lower extent of sites with iCAL ≥3 mm as compared with lower-frequency cleaning (1 to 3×/wk; P ≤ 0.05). Interdental cleaning users showed lower numbers of coronal caries, interproximal coronal caries, and missing teeth as compared with nonusers ( P < 0.0001). Nonusers had 1.73-times (95% confidence interval, 1.53 to 1.94) higher odds for having ≥1 surfaces of coronal caries as compared with interdental cleaning users, regardless of the weekly frequency. Individuals were less likely to be in diseased PPCs if they were interdental cleaning users. Low-frequency cleaners (1 to 3×/wk) had significantly greater odds (1.43; 95% confidence interval, 1.08 to 1.88) to have severe disease (PPC-G) versus health (PPC-A) than were high-frequency cleaners (4 to 7×/wk). Interdental cleaning users showed lower levels of periodontal disease and caries and lower numbers of missing teeth. Higher frequency of interdental cleaning was correlated with increased periodontal health. Individuals with severe periodontal disease could show additional oral health benefits by increasing cleaning frequency. The data support the use of interdental cleaning devices as an oral hygiene behavior for promoting health.